PENGEMBANGAN KOMPETENSI PEGAWAI APARATUR SIPIL NEGARA (ASN) SEKOLAH TINGGI AGAMA ISLAM NEGERI (STAIN) CURUP MELALUI METODE PENDIDIKAN DAN PELATIHAN - Irwan Fathurrochman (UNIVERSITAS BENGKULU, 2017)
Development of employee competency State Civilian Officials (ASN) basically aims to ensure and maintain the ability of employees to meet the qualifications so as to provide optimal contribution to the organization. One form of employee development is education and training. Education and training can through off the job and on the jobtraining. Off the jobtraining namely the approach of training outside the workplace that provide opportunities for employees to get out of the routine of work and concentrate in studying something related to work. While on the job training approach is the approach of the training provided to adjust working methods, adaptation to the job, using the media work or work tools directly.